Incomplete Multi-View Multi-Label Classification via Diffusion-Guided Redundancy Removal - Ou, Shilong; Xue, Zhe; Qin, Lixiong; Li, Yawen; Liang, Meiyu; Wu, Junjiang; Zhang, Xuyun; Beheshti, Amin; Qi, Yuankai (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Incomplete multi-view multi-label classification aims to accurately predict labels for each sample in the face of some missing views. Due to its widespread presence in real-world scenarios, it has become an extensively researched topic. In addition to the challenges brought by missing views, it also encounters issues caused by redundant views, whose inclusion fails to make a positive contribution to performance. In this paper, we make the first attempt to take advantage of diffusion models to address the missing view problem and design a strategy to identify and remove redundant views. Specifically, we train a diffusion model conditioned on the pseudo-labels to recover information of missing views. The learned diffusion model can carry data distribution knowledge in training split to the data. Regarding redundant identification strategy, it is designed by considering both the additional information of views and the classification difficulty level of samples, thereby adaptively identifying and removing redundant views. We conduct extensive experiments on five datasets, and the proposed method achieves favorable performance against several state-of-the-art methods on the multi-view multi-label classification task.